Território e subjetividade: reflexões sobre a cidade que pulsa ao ritmo da desigualdade social - Santos, Gabriela Moreira Rodrigues dos (2022)
The present work intends to contribute to the reflexion on how the conditions of specific urban areas interfere on the subjectivity of the inhabitants and aims to investigate the influence of the experiences lived in the cities over the people, focusing on the emotional and psychosocial dimensions. The importance of this investigation is directly associated to the main role of the affections towards the recognition of the ethical dimension of the life, as well as its imperative influence to the rise of people's emancipatory and innovative ideas and actions, that are mandatory for the improvement of the social reality. The study is based on theoretical discussions on the subjectivity social character and on important concepts for the comprehension of urban's life, such as, property, urbanism, territory and city. We also introduce relevant cases about different cities and theoretical contributions to the study of people's lives in the cities from the analysis of the concepts as life experiences, emotion, affection and ethical political suffering. The theoretical referential used consisted of the theoretical elaborations of Espinosa, Ribot, Sawaia and Vigotski. As a research method we analyzed reports of São Paulo City residents about the place they live in, based on the creation of analytical categories. In this research we observed that the experiences of living in the cities are influenced by several factors, directly bound to the structure of the territories and their capacity to correspond to the social demands of reducing the condition of exclusion. Finally, we concluded that it is essential to consider the affective reactions of citizens in the planning of urban spaces and the public policies to them associated